FRI0150 Chronic Back Pain (CBP) Characteristics Associated with the Presence of Sacroiliitis on Magnetic Resonance Imaging (MRI) in Patients with Suspected Axial Spondyloarthritis (AXSPA): Results from the Esperanza Cohort. (10th June 2014) - Navarro-Compán, V.; Almodόvar, R.; Hernández, A.; Beltrán, E.; de Miguel, E.; Zarco, P.
Abstract : Background: CBP is nowadays the starting point for the ASAS classification criteria for axSpA. Later, two possible entry criteria based on complementary examinations (imaging and HLA-B27) are considered. CBP is a very prevalent symptom, so it is necessary to identify those characteristics more likely resulting in a positive complementary test. Objectives: To evaluate which inflammatory characteristics of CBP are associated with the presence of sacroiliitis on MRI in patients with suspected axSpA. Methods: Baseline dataset from the EsPeranza cohort (<45 years old, symptoms duration 3-24 months and with inflammatory back pain -IBP- or asymmetrical arthritis or spinal/joint pain plus ≥1 SpA features) was used. Data from 326 patients with axial symptoms who underwent sacroiliac joint (SIJ) MRI were analysed. Odds ratio were estimated for the association between IBP characteristics (morning stiffness, improve with exercise and not with rest, alternating buttock pain, insidious onset, awakening at 2nd half of night and good response to NSAID) and their different combinations with a positive SIJ MRI (ASAS definition). Results: A total of 130 (40%) patients had sacroiliitis.Table shows the results for the association between the individual and combined IBP characteristics with a positive MRI. Alternating buttock pain (OR=3.43; p<0.001), insidious onset (OR=2.15; p<0.05) and awakening at 2nd half of the night (OR=1.71; p<0.05) were associated with a positive MRI. The combination of these characteristics or the addition of alternating buttock pain to the ASAS definition of IBP were the most specific (OR=3.08; p<0.001; Spe 92% and OR=6.17; p<0.001; Spe 94%, respectively). Conclusions: Alternating buttock pain is the IBP characteristic most strongly associated with a positive SIJ MRI in patients with suspected axSpA. The inclusion of this characteristic in the current definition of IBP could improve the efficiency of SIJ MRI. Acknowledgements: The EsPeranza Program has been supported by an unrestricted grant from Pfizer Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1768